2008
DOI: 10.1021/ja711480f
|View full text |Cite
|
Sign up to set email alerts
|

An ICT-Based Approach to Ratiometric Fluorescence Imaging of Hydrogen Peroxide Produced in Living Cells

Abstract: We present the synthesis, properties, and biological applications of Peroxy Lucifer 1 (PL1), a new fluorescent probe for imaging hydrogen peroxide produced in living cells by a ratiometric response. PL1 utilizes a chemoselective boronate-based switch to detect hydrogen peroxide by modulation of internal charge transfer (ICT) within a 1,8-naphthalimide dye. PL1 features high selectivity for hydrogen peroxide over similar reactive oxygen species, including superoxide, and nitric oxide, and a 65 nm shift in emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
290
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 515 publications
(298 citation statements)
references
References 24 publications
3
290
0
2
Order By: Relevance
“…Accordingly, we developed a unique H 2 O 2 -specific fluorescent indicator, PY1-ME (Fig. S1A), which combines a boronate-masked phenol for the selective detection of H 2 O 2 (10,(33)(34)(35)(36)(37)(38)(39) and an appended methyl-ester group designed to increase cellular uptake and retention upon cleavage by intracellular esterases; this latter feature makes the dye suitable for both fluorescence imaging and flow cytometry experiments. Because this probe relies on a specific molecular reaction between H 2 O 2 and the boronate to generate a fluorescence signal, rather than thiol-based chemistry that can occur by non-specific ROS oxidation or disulfide exchange, our chemical method affords a direct measure of H 2 O 2 in cellular specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we developed a unique H 2 O 2 -specific fluorescent indicator, PY1-ME (Fig. S1A), which combines a boronate-masked phenol for the selective detection of H 2 O 2 (10,(33)(34)(35)(36)(37)(38)(39) and an appended methyl-ester group designed to increase cellular uptake and retention upon cleavage by intracellular esterases; this latter feature makes the dye suitable for both fluorescence imaging and flow cytometry experiments. Because this probe relies on a specific molecular reaction between H 2 O 2 and the boronate to generate a fluorescence signal, rather than thiol-based chemistry that can occur by non-specific ROS oxidation or disulfide exchange, our chemical method affords a direct measure of H 2 O 2 in cellular specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The Cell-IQ analyzer software utilizes machine vision to automatically identify and quantify cell types. Near-infrared fluorescence(NIRF)probe [49] Fluorescent protein Two-photon fluorescent probe [64,76] Quantum dot (QDs) probes [42,43] pH sensitive probe [51,52,95] Gold nanoparticles [83] Nanoparticles Magnetic nanocrystal [84] Proteins Direct observation of molecular dynamics can provide important information about cellular events that cannot be obtained by other methods. Thus imaging of protein dynamics in living cells becomes an important tool for cell biology to study molecular and cellular functions.…”
Section: Probe Sortingmentioning
confidence: 99%
“…BODIPY-alphaTocopherol adduct (B-TOH), a novel lipophilic fluorescent antioxidant indicator, is a sensitive and specific probe enabling the molecular imaging of peroxyl radicals in the lipid membranes of live cells [63]. Two-photon confocal microscopy experiments in live macrophages showed that Peroxy Lucifer 1 (PL1), which is a newly synthezied fluorescent probe for imaging hydrogen peroxide produced in living cells by a ratiometric response, can ratiometrically visualize localized hydrogen peroxide bursts generated in living cells at immune response levels [64]. Luminescence analysis has been recently proposed to measure free radical generation by isolated cells or organs, but it allowed only global tissue luminescence.…”
Section: Radicalsmentioning
confidence: 99%
“…Whereas many of them only utilized the changes in emission intensity as detecting signals. A major limitation of the intensity-based fluorescent probe is that the signal output could be interfered by the factors such as environmental conditions, probe distribution, and instrumental efficiency [9,10]. By contrast, a ratiometric measurement, employing the ratio of two emissions at different wavelengths as the detecting signal, could provide a built-in correction for the above mentioned factors and thus allow more accurate analysis [11,12].…”
Section: Introductionmentioning
confidence: 99%